Direct response to Notch activation: signaling crosstalk and incoherent logic. - Krejcí, A.; Bernard, F.; Housden, B.E.; Collins, S.; Bray, S.J. (Science signaling, 2009)
Notch is the receptor in one of a small group of conserved signaling pathways that are essential at multiple stages in development. Although the mechanism of transduction impinges directly on the nucleus to regulate transcription through the CSL [CBF-1/Su(H)/LAG-1] [corrected] DNA binding protein, there are few known direct target genes. Thus, relatively little is known about the immediate cellular consequences of Notch activation. We therefore set out to determine the genome-wide response to Notch activation by analyzing the changes in messenger RNA (mRNA) expression and the sites of CSL occupancy within 30 minutes of activating Notch in Drosophila cells. Through combining these data, we identify high-confidence direct targets of Notch that are implicated in the maintenance of adult muscle progenitors in vivo. These targets are enriched in cell morphogenesis genes and in components of other cell signaling pathways, especially the epidermal growth factor receptor (EGFR) pathway. Also evident are examples of incoherent network logic, where Notch stimulates the expression of both a gene and the repressor of that gene, which may result in a transient window of competence after Notch activation. Furthermore, because targets comprise both positive and negative regulators, cells become poised for both outcomes, suggesting one mechanism through which Notch activation can lead to opposite effects in different contexts.